2013
DOI: 10.1264/jsme2.me13066
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Abundance of Archaeal and Bacterial Ammonia Oxidizers in the Sediments of the Dongjiang River, a Drinking Water Supply for Hong Kong

Abstract: Ammonia-oxidizing archaea (AOA) and bacteria (AOB) play important roles in nitrification. However, limited information about the characteristics of AOA and AOB in the river ecosystem is available. The distribution and abundance of AOA and AOB in the sediments of the Dongjiang River, a drinking water source for Hong Kong, were investigated by clone library analysis and quantitative real-time PCR. Phylogenetic analysis showed that Group 1.1b-and Group 1.1b-associated sequences of AOA predominated in sediments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…5a; see also Table S5 in the supplemental material). Although the sequences affiliated with this marine AOA-associated lineage have been obtained from neutral or only slightly acidic environments (43)(44)(45), the evidence directly linking this group to ammonia oxidation was missing. Thus, a greater physiological versatility of this marine lineage was observed in this study, despite reduced labeling compared to that of AOA associated with soil group 1.1b.…”
Section: Discussionmentioning
confidence: 99%
“…5a; see also Table S5 in the supplemental material). Although the sequences affiliated with this marine AOA-associated lineage have been obtained from neutral or only slightly acidic environments (43)(44)(45), the evidence directly linking this group to ammonia oxidation was missing. Thus, a greater physiological versatility of this marine lineage was observed in this study, despite reduced labeling compared to that of AOA associated with soil group 1.1b.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of sediment ammonia-oxidizing archaeal and bacterial populations has been investigated in a variety of freshwater ecosystems, such as river (Reis et al 2015;Sonthiphand et al 2013;Sun et al 2013;Xie et al 2014), reservoir , lake (Bollmann et al 2014;Hou et al 2013;Liu et al 2015;Mukherjee et al 2016;Zhao et al 2013Zhao et al , 2014, wetland (Liu et al 2014a;Wang et al 2013;Yang et al 2014), and pond (Lu et al 2015), yet the relative importance of AOA and AOB to nitrification process in freshwater sediments remains under debate. Several previous studies indicated that AOA amoA gene abundance was usually greater than AOB in lake sediments (Herrmann et al 2009;Hou et al 2013;Zhao et al 2014), while the numerical dominance of AOB over AOA amoA gene abundance was observed in sediments of many freshwater lakes on the Yunnan Plateau (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…pH significantly affected the AOA community in river sediments [20]. Elevated temperature increased AOA abundance, whereas it decreased AOB abundance [30].…”
mentioning
confidence: 98%
“…It has been found that AOA dominated in marine sediments [1,17], indicated by its better adaptation to anaerobic, low pH, and low ammonia habitats than AOB [18][19], whereas higher nutrients in the freshwater sediments promoted AOB dominance, such as river sediments [20], mangrove sediments [16,21], and shore side wetlands [22]. Zhao et al [13] found that the abundance of archaeal amoA in lake sediment was higher than bacterial amoA, whereas Moiser and Francis [23] found that bacterial amoA copy numbers were greater than archaeal amoA in most of the estuary.…”
mentioning
confidence: 99%